Workshop Analisis Butir Soal Bagi Guru Sekolah Menengah Kejuruan Negeri 6 Kota Jambi - Arpizal, Arpizal; Suratno, Suratno; Liputo, Muhammad Arif; Refnida, Refnida (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
To determine the success of the education program, high-quality test instruments are necessary, namely those that are valid, reliable, have a sufficiently good level of difficulty, and can differentiate between the learning outcomes of proficient and non-proficient students. Ideally, these questions should be prepared by economics teachers. In reality, however, many teachers generally do not know how to prepare good questions. This is closely related to teachers' activities, which have been primarily focused on meeting learning targets alone. This is the source of the problem because teachers are rarely given the opportunity to prepare high-quality questions. To address this issue, this Professional Development Program (PPM) is implemented. The main target of the activity is teachers from Vocational High School 6 in Jambi City, with a total of 20 participants. The expected outcome of the training is that participants can compose questions that meet quality standards. The training results show that the average knowledge score of participants regarding item analysis before the training is 61.50, and after the training, it increases to an average score of 80. This indicates an increase in knowledge scores by 30.08%. In general, participants are now able to manually conduct item analysis effectively, but some still face difficulties in analyzing question validity, reliability, and distractor analysis.